DAMPAK DRAMA KOREA TERHADAP PENDIDIKAN AKHLAK REMAJA DI PERUM TAMAN SINGAPERBANGSA TELUKJAMBE TIMUR KARAWANG - Sari, Dinda Rahma; Masykur, Masykur; Kosim, Abdul (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2024)
In Islam, character education is essential for a child's future, therefore from an early age children are taught how to have good morals. However, when they become teenagers, they will find many things that make them waver, they start to change what has been ingrained in them, one of which is by watching Korean dramas, this influences the moral education of teenagers, many of them prefer to postpone their worship because they are too focused on Korean dramas. Then many of them also imitate the behavior of Korean drama characters such as how they dress, accessories, food and even use Korean in their daily lives. This research uses a qualitative method with a phenomenological approach to social construction. Data collection uses interviews and observations of teenagers. The results of the research show that: 1) Korean dramas have a significant impact on the moral education of teenagers, 2) By watching Korean dramas, many teenagers are neglectful of their worship, follow the Korean way of dressing, are carried away emotionally by the stories in them and often use Korean. The implications of this research are: 1) increasing moral awareness, 2) educating parents and youth companions, 3) developing educational materials, 4) monitoring social media, 5) developing media literacy, 6) promoting local culture, 7) school collaboration and family.